COMPUTED TOMOGRAPHY (CT) FINDINGS OF SCHIZOPHRENIC PATIENTS AFTER LONG TIME FROM PSYCHOSURGERY - OGASHIWA, Motohide; MURAKAMI, Hiroshi; ADACHI, Naoto; AKASHI, Toshio; TOYODA, Junzou (Japanese Journal of National Medical Services, 1991)
The CT findings on 20 chronic schizophrenic inpatients who had undergone psycho-surgery 37 years ago (operated group) were compared to 20 chronic schizophrenic inpa-tients without psychosurgery (non-operated group). The subjects of non-operated group were selected by matched age, sex and duration of the illness. Operated group showed significant decrease in frontal lobe size (p<0.001), enlargement of frontal horns of the lateral ventricle (p<0.01), widening of interhemispheric fissure (p<0.05) and brain atrophy (p<0.001) in comparison with non-operated group. Size of surgical injury showed significant rank correlation to frontal lobe size (p<0.01) and brain atrophy (p<0.001). Regarding the horizontal level of injury, in comparison with non-operated group, the patients with deficit in higher frontal areas showed enlargement of lateral ventricles (p<0.01) and those with deficit in lower frontal areas showed widening of interhemispheric fissure (p<0.05). Regarding the laterality of injury, the patients with deficit in left hemisphere showed significantly widened sylvian fissure in comparison with non-operated group (p<0.05).